The Effectiveness Of Puzzle Games On Development Fine Motor Skills Of Pre-School Children Age 3-6 Years - Syazana, Defi; Purba, Andareas Kiser; Milanda, Metha Arian; Afdwikki, Muhammad Izha; Prima Aulia (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
At the preschool age, between the ages of 3-6 years, the child's fine motor skills begin to develop, where the child begins to be able to draw and write. Educational media games can be used as a fine motor skills for children, one of which is a puzzle game. This study aims to look at the effectiveness of puzzle games against fine motor development in children aged 3-6 years. The research uses a quasi-experimental method with a pretest-posttest control group design. The sample of this research is an entire pre-school child in PAUD Tunas Bangsa of 20 children. The data were analyzed using the Shapiro-Wilk normality test, the Mann-Whitney hypothesis test, and the Cohen's Effect Size calculation. The results of the hypothetical test showed that there was a significant improvement in fine motor skills development in the experimental class (p-value < 0,001), whereas in the control class there was no significant increase (p -value = 0,842). The conclusion of this study is that puzzle games are effective in improving fine motor skills development of pre-school children aged 3-6 years.